COVID-19 disease outcomes in patients receiving clozapine versus other antipsychotics: a national study in Qatar - Albahari, Dalia; Abdalla, Oraib; Alqam, Shatha Mahmud Ismail; Mohammed, Mohammed Faisal Hamad; Ahmed, Mohamed Ali Siddig; Wadoo, Ovais (Frontiers in Psychiatry, 2025)
BackgroundClozapine has immunomodulatory effects that raised concerns about its potential to exacerbate severe COVID-19. This study examines whether clozapine use is associated with worse COVID-19 outcomes in patients with schizophrenia.MethodsThis retrospective cohort study compared COVID-19 outcomes in SARS-CoV-2-infected patients on clozapine versus those on other antipsychotics. Primary outcomes included severe disease, hospitalization, ICU admission, and mortality. Descriptive statistics summarized the data, with categorical variables analyzed via Chi-square tests and exact Fisher test. The continuous variables were analyzed via Student’s t-test. Logistic and linear regression analyses estimated odds ratios while adjusting for confounders.ResultsThirty-three patients on clozapine (29.7%) tested positive for SARS-CoV-2 and were compared to 132 SARS-CoV-2-positive patients on non-clozapine antipsychotics. Severe infection rates did not significantly differ (clozapine: 3%, non-clozapine: 7.69%, p = 0.340), nor did hospitalization rates (clozapine: 15.1%, non-clozapine: 16.9%, p = 0.807). All clozapine patients survived, while one death (0.7%) occurred in the non-clozapine group. The mean hospital stay was similar (clozapine: 8.8 days, SD = 2.2; non-clozapine: 11.5 days, SD = 1.9; p = 0.515). Logistic regression, correcting for age, sex, vaccination status, medical comorbidities, obesity, and smoking, found no significant associations: odds ratio for severe COVID-19 = 1.9 (95% CI: 0.1–12.0, p = 0.94); odds ratio for hospitalization = 0.96 (95% CI: 0.23–3.96, p = 0.953). Linear regression of hospital stay duration yielded a β-coefficient of 4.6 (95% CI: -9.4–18.7, p = 0.471). Peri- and post-infection white blood cell and neutrophil counts were not significantly different (p = 0.4298 and p = 0.1434, respectively).ConclusionClozapine use was not associated with worse COVID-19 outcomes, supporting its relative safety during SARS-CoV-2 infection. These findings reassure clinicians regarding clozapine’s continued use in treatment-resistant schizophrenia. However, the small clozapine sample size limits statistical power, warranting cautious interpretation and further research.